Discrete event simulation and optimization for DOS in a public hospital - Chen, Zitong (2019)
Through the research and learning in this Final Year Project (FYP), an aggregate stochastic model for the Department of Surgery (DOS) based on a careful study of data on individual patient arrival times, length of stay (LOS) and discharge time has been built and validate. By using this model, we simulated data and applied a greedy algorithm to find the optimal bed allocation which maximize utilization of resources in the public hospital. A Discrete Event Simulation (DES) model based on SimPy has also been build according to the workflow in DOS including consideration of the process inside Operation Theatre (OT), however, due to lack of information, we have not put it into practice while its advantage and necessity has been studied to prove it is powerful for future use.